1980
DOI: 10.1258/002367780781071094
|View full text |Cite
|
Sign up to set email alerts
|

Clinical ocular findings in a colony of chinchillas (Chinchilla laniger)

Abstract: Examination of 14 aged chinchillas revealed a shallow orbit, a rudimentary nictitating membrane, a large cornea, a densely pigmented iris with a vertical slit pupil, and an anangiotic fundus with variable vascularization of the optic disc. Mean intraocular pressure was 18.5 /+- 5.75 standard deviation mmHg. Bilateral posterior cortical cataracts and asteroid hyalosis were observed in 2 animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 6 publications
4
29
0
Order By: Relevance
“…The average IOP value was smaller than that which was previously estimated by applanation tonometer in chinchillas (PEIFFER & JOHNSON, 1980;LIMA et al, 2010). Because differences have been observed between applanation tonometry and rebound tonometry, the results of one method cannot be applied to another.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The average IOP value was smaller than that which was previously estimated by applanation tonometer in chinchillas (PEIFFER & JOHNSON, 1980;LIMA et al, 2010). Because differences have been observed between applanation tonometry and rebound tonometry, the results of one method cannot be applied to another.…”
Section: Discussionmentioning
confidence: 56%
“…Chinchillas are bred for the fur trade, employed as a model in ophthalmic research and produced increasingly as pets (PEIFFER & JOHNSON, 1980;WILLIAMS, 2007;MÜLLER et al, 2010, MÜLLER & EULE, 2014. Moreover, studies describing ophthalmic parameters in chinchillas are scarce (PEIFFER & JOHNSON, 1980;LIMA et al, 2010;MÜLLER et al, 2010;BERCHT et al, 2015).…”
Section: Clinic and Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Food and hair impaction into periodontal pockets can also lead to lateral and tooth root abscessation (Hoefer and Crossley, 2002). Peiffer and Johnson (1980) examined the eyes of 14 chinchillas, ages 6-17 years old. 9.10) or CT of the skull to best assess the extent of tooth root abnormalities is strongly recommended (Donnelly, 2004).…”
Section: Malocclusionmentioning
confidence: 99%
“…In addition to humans, AH has been observed in dogs, 31,32 chinchillas, 33 cats, 32 and rabbits. 34 While none of these specific animals consistently develop bilateral AH, we have observed that young (9-month old or less) male beagles fed a diet containing 30% galactose for 42 months all developed AH.…”
Section: The Galactose-fed Dogmentioning
confidence: 99%